Factors affecting exchange rate in Southeast Asian countries / Nurfara Inani Ismail and Norsikin Abu Othman - Ismail, Nurfara Inani; Abu Othman, Norsikin (Faculty of Business and Management, 2015)
The aim of this study is to investigate factors affecting exchange rate in Southeast Asian countries. The dependent variable of this study is exchange rate while independent variables are interest rate, term of trade and external debt. The sample of study consists of four Southeast Asian countries which are Malaysia, Thailand, Indonesia and Philippine and data collected covers the period from 1992 until 2012. This study employs Panel Regression Random Effect Model in order to study the relationship between those variables. The result of this study found that only external debt has positive significant relationship with exchange rate while interest rate and term of trade do not have significant relationship with exchange rate.